The needs of data protection against cyber interference: Study in Multimedia University / Nur Afiqah RJ. Mohamad...[et.al] - RJ. Mohamad, Nur Afiqah; Mohamad Suraji, Norliana Amira; Adnan, Nurfarahin; Mahmood, Ain Nabilah (2015)
This research the level of awareness among MMUs staff about data protection and policy used in organization. The researcher wants to know whether the MMU's staff alert about the existence in data protection. Based on the hypothesis in this research shows that staffs lack of awareness about data protection can lead to cyber interference. For the second hypothesis is the policy that has been implemented affects the organization. The researcher was conducting the survey by using the questionnaire that had been distributed to the staff in University: Do you know about data protection? Do you know data content in data protection? Do you know about personal Data protection Act 2010? Where do you get the information about data protection? An analysis of the data revealed that almost of staff in IT department aware about data protection in MMU's but them not clear about function and content about data protection. It was recommended that have a good practices and education about data protection. In addition. referring the expertise Can assist the policy maker to create better and understanding policy. The policy used in the organization should be improvised and enforce.